Sequential therapy with darolutamide in patients with non‐metastatic castration‐resistant prostate cancer resistant to enzalutamide or apalutamide - Saizo Fujmoto; Kazutoshi Fujita; Mitsuhisa Nishimoto; Mamoru Hamaguchi; Ken Kuwahara; Mamoru Hashimoto; Shogo Adomi; Takafumi Minami; Masahiro Nozawa; Kazuhiro Yoshimura; Hirotsugu Uemura (Cancer Medicine)
Abstract Enzalutamide, apalutamide, and darolutamide are currently recommended for patients with non‐metastatic castration‐resistant prostate cancer (nmCRPC), but cross‐resistance of androgen receptor‐axis‐targeted therapies (ARAT) occurs. Because darolutamide has a distinct chemical structure to other non‐steroidal antiandrogens, it may be effective for nmCRPC patients resistant to enzalutamide or apalutamide. We retrospectively evaluated the efficacy of switching to darolutamide in patients with nmCRPC. We included nine nmCRPC patients who experienced biochemical progression on enzalutamide or apalutamide and were switched over to darolutamide. Five patients (55.5%) had a PSA response >50% decline after starting darolutamide, with an average of 73% PSA decline. Median progression‐free survival was 6 months. In conclusion, an ARAT switch from enzalutamide or apalutamide to darolutamide might be effective for nmCRPC. Although the validation in a large‐scale cohort is necessary, the switch to darolutamide could be a promising therapeutic option after the progression of 1st line ARAT in nmCRPC patients.